The Norwegian CCS Research Centre (NCCS): facilitating industry-driven innovation for fast-track CCS deployment. Issue 2 (8th March 2020) - Brunsvold, Amy; Tangen, Grethe; Størset, Sigmund Ø; Dawson, James; Braathen, Alvar; Steenstrup-Duch, Anne; Aarlien, Rune; Mølnvik, Mona J
Abstract : The NCCS is an international Centre for Environment-friendly Energy Research addressing CO2 CCS—key technology in the portfolio of measures instrumental in all energy scenarios outlining conceivable paths to curb global warming. Graphical Abstract: